Police Reform and the Dismantling of Legal Estrangement - Bell, Monica C (2017)
In police reform circles, many scholars and policymakers diagnose the frayed relationship between police forces and the communities they serve as a problem of illegitimacy, or the idea that people lack confidence in the police and thus are unlikely to comply or cooperate with them. The core proposal emanating from this illegitimacy diagnosis is procedural justice, a concept that emphasizes police officers' obligation to treat people with dignity and respect, behave in a neutral, non-biased way, exhibit an intention to help, and give them voice to express themselves and their needs, largely in the context of police stops. This Essay argues that legitimacy theory offers an incomplete diagnosis of the policing crisis, and thus de-emphasizes deeper structural, group-centered approaches to the problem of policing. The existing police regulatory regime encourages large swaths of American society to see themselves as existing within the law's aegis but outside its protection. This Essay critiques the reliance of police decision makers on a simplified version of legitimacy and procedural justice theory. It aims to expand the predominant understanding of police mistrust among African Americans and the poor, proposing that legal estrangement offers a better lens through which scholars and policymakers can understand and respond to the current problems of policing. Legal estrangement is a theory of detachment and eventual alienation from the law's enforcers, and it reflects the intuition among many people in poor communities of color that the law operates to exclude them from society. Building on the concepts of legal cynicism and anomie in sociology, the concept of legal estrangement provides a way of understanding the deep concerns that motivate today's police reform movement and points toward structural approaches to reforming policing